The L1-type cell adhesion molecule neuroglian influences the stability of neural ankyrin in the Drosophila embryo but not its axonal localization. - Bouley, M.; Tian, M.Z.; Paisley, K.; Shen, Y.C.; Malhotra, J.D.; Hortsch, M. (Journal of Neuroscience, 2000)
Ankyrins are linker proteins, which connect various membrane proteins, including members of the L1 family of neural cell adhesion molecules, with the submembranous actin-spectrin skeleton. Here we report the cloning and characterization of a second, novel Drosophila ankyrin gene (Dank2) that appears to be the result of a gene duplication event during arthropod evolution. The Drosophila L1-type protein neuroglian interacts with products from both Drosophila ankyrin genes. Whereas the previously described ankyrin gene is ubiquitously expressed during embryogenesis, the expression of Dank2 is restricted to the nervous system in the Drosophila embryo. The absence of neuroglian protein in a neuroglian null mutant line causes decreased levels of Dank2 protein in most neuronal cells. This suggests that neuroglian is important for the stability of Dank2 protein. However, neuroglian is not required for Dank2 axonal localization. In temperature-sensitive neuroglian mutants in which neuroglian protein is mislocated at the restrictive temperature to an intracellular location in the neuronal soma, Dank2 protein can still be detected along embryonic nerve tracts.